A cross-sectional survey of prospective healthcare professionals' knowledge, attitudes and perceptions of medical Cannabis - Satish Jankie; Keshav Sewdass; William Smith; Candy Naraynsingh; Jenelle Johnson; Niall Farnon; Kavita Mahadeo; Shastri Motilal (Elsevier, 2023)
Background: Compounds isolated from Cannabis possess many beneficial effects creating a renewed worldwide interest in its therapeutic potential. With increased legalization for medicinal use globally, healthcare professionals must be familiar with the drug's uses and potential adverse effects. Objective: To determine prospective healthcare providers' knowledge, attitude and perception to medical Cannabis. Method: A self-administered online questionnaire comprising 21 questions to assess the knowledge, attitude and perception of medical Cannabis was distributed via google forms among students at the Faculty of Medical Sciences, the University of the West Indies, St Augustine Campus. Chi-square analysis was used to detect significant associations between demographics and measured variables. A p-value <0.05 was considered significant. Results: Popular perceived therapeutic benefits of Cannabis were chronic pain (91.2%), anxiety (84.2%) and seizures (71.1%), and identification of the risks associated with the use of Cannabis was low. Users of Cannabis were able to identify indications and symptoms that can be treated with Cannabis but were less aware of the adverse effects of the drug than non-users (p < 0.001). More than three-quarters (87.3%) believed they could identify therapeutic uses and adverse effects but only 14.2% were ready to answer queries from patients. The main source of Cannabis information was the internet and information was lacking in the medical school curriculum. Conclusion: The majority of students could not identify the drug's indications and adverse effects. There is a need to improve training for all prospective medical personnel to cater for the change in legislation status.